RESEARCH VERB LEXICONS IN ENGLISH ACADEMIC WRITINGS - Hayati, Noor Maulida; Sutrisno, Adi (Prologue: Journal on Language and Literature, 2024)
This research aims to identify the verb lexicon used in English academic writing by students in Indonesia. The verbs that have been found are called research verbs and then the meaning and concept of each verb is explained. Apart from that, this research also aims to compile the explication of each verb using the Natural Semantic Metalanguage approach. The research data is in the form of research verbs which have been filtered and the ten words with the highest frequency of appearance in a number of research articles have been taken. The data source is Indonesian student research articles written in English within the field of English Education and Literature. The data collection method was carried out using corpus techniques using the LancsBox 6.0 corpus engine. The data analysis method uses Anna Wierzbicka's Natural Semantic Metalanguage theory and the explication conduction uses Wierzbicka and Goddard's semantic primes. The research results reveal that there are ten research verbs that appear most frequently in students' academic articles. Each word has its meaning and concept explained and an explanation of the meaning is prepared in a universal language so that it can be understood by all language speakers.